Comparison of Strain Histories on Reinforced Concrete Eccentric Braced Frame (EBF) With Vertical and Horizontal Link - Wijaya, Ming Narto; Susanti, Lilya; Pinontoan, Frisca Presley (Rekayasa Sipil, 2025)
This study investigates the seismic performance of reinforced concrete Eccentrically Braced Frames (EBF) with vertical and horizontal link beams subjected to cyclic loading. The main objective is to compare strain histories and evaluate energy dissipation in vertical and horizontal link configurations. Experimental results indicate that vertical links, especially those with shorter lengths (15 cm), exhibit higher strain values, leading to significant plastic deformation and enhanced energy dissipation, though at the cost of increased damage and repair needs. Conversely, horizontal links remain largely within the elastic range, maintaining better structural integrity but offering less energy dissipation during seismic events. The CBF (Concentrically Braced Frame) control specimen showed minimal deformation and lower energy absorption. The findings suggest that vertical links are more suitable for energy dissipation in seismic design, while horizontal links offer greater durability and lower post-event maintenance. The balance between energy absorption and repairability is crucial for optimizing EBF systems in earthquake-prone areas. (explain the findings related to the purpose of this paper: to determine the effects of link orientation on strain distribution, energy dissipation, and structural integrity during seismic events).